Patients’ Cataract Knowledge, Post-Surgery Anxiety and Patiens’ Satisfaction of Cataract Surgery in Surabaya General Hospital: Preliminery Study - Taufiq, Isa; Setiyowati, Eppy; Ernawati, Yayuk; Hidayatullah, Achmad; Nadatien, Ima; Umamah, Faridah (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Patients’ knowledge about cataracts, post-surgery anxiety and the satisfaction of cataract surgery services influence psychologist readiness, obedience, and all surgical experience. Understanding these factors are significant to design education intervention and effective perioperative psychosocial. The study aims: This cross-sectional descriptive preliminary study aimed to describe knowledge level, post-surgery anxiety and patients’ satisfaction of cataracts surgery in Surabaya General Hospital on September 2025, in order to identify problems description which need service improvement. Method: This was consecutive samples of 56 cataract surgery patients. Data collected by structured knowledge questionnaire (validated; KR-20 = 0.82), Zung Self-Rating Anxiety Scale (ZSAS; α = 0.88), and Patients’ Satisfaction Questionnaire (PSQ 2017) adapted from PSQ-18 (α = 0.91). Analysis data found descriptively as frequency, percentage, average, and deviation standard. Result: Most of the participants are female (58.9 %), aged 60-69 years old (48.2 %), and educated from low to medium level. The knowledge level which good is on 50.0 % of the participants (average 11.5 ± 2.0 from 15), medium level is on 17.9 %, and low level is on 32.1 %. Post-surgery anxiety in zero level is 53.6 % (average 45.0 ± 8.0), minor level is on 21.4 %, and major level is on 25.0 %. Major level satisfaction is on 58.9 % (average 39.5 ± 6.0 from 50), medium level is on 16.1 %, and minor level is on 25.0 %. Lower education level and informal job related by lower knowledge and satisfaction. Conclusion: This study shows mostly of the cataract surgery patients have lack of knowledge, major post-surgery anxiety, and low satisfaction. It needs better education intervention and appropriate, intense psychosocial support system as well. This finding gives prime important to serious discrepancy on the preparation and patients treatments nowadays, that needs further study and refinement to optimize patients’ results and all experience of health services